Achieving 37.1% Green Electroluminescent Efficiency and 0.09 eV Full Width at Half Maximum Based on a Ternary Boron‐Oxygen‐Nitrogen Embedded Polycyclic Aromatic System - Cai, Xinliang; Xue, Jianan; Li, Chenglong; Liang, Baoyan; Ying, Ao; Tan, Yao; Gong, Shaolong; Wang, Yue (Angewandte Chemie International Edition, 2022)
Herein, a ternary boron‐oxygen‐nitrogen embedded polycyclic aromatic hydrocarbon with multiple resonance thermally activated delayed fluorescence (MR‐TADF), namely DBNO, is developed by adopting the para boron‐π‐boron and para oxygen‐π‐oxygen strategy. The designed molecule presents a vivid green emission with a high photoluminescence quantum yield (96 %) and an extremely narrow full width at half maximum (FWHM) of 19 nm/0.09 eV, which surpasses all previously reported green TADF emitters to date. In addition, the long molecular structure along the transition dipole moment direction endows it with a high horizontal emitting dipole ratio of 96 %. The organic light‐emitting diode (OLED) based on DBNO reveals a narrowband green emission with a peak at 504 nm and a FWHM of 24 nm/0.12 eV. Particularly, a significantly improved device performance is achieved by the TADF‐sensitization (hyperfluorescence) mechanism, presenting a FWHM of 27 nm and a maximum external quantum efficiency (EQE) of 37.1 %. A ternary B−O−N embedded multiple resonance thermally activated delayed fluorescence emitter is developed based on the para B‐π‐B and O‐π‐O strategy. It exhibits a narrowband green emission with a full width at half maximum (FWHM) of 19 nm/0.09 eV and a preferential horizontal dipole ratio of 96 %. The corresponding organic light‐emitting diode (OLED) emits green light with a FWHM of 27 nm and a high external quantum efficiency (EQE) of 37.1 %.